A Review Of The Effects And Behaviour Of Nickel During Gold Cyanidation, Adsorption, Acid Washing, Elution, Electrowinning, And Zinc Precipitation - A. C. Bax; M. C. Costello; S. R. LaBrooy (Society for Mining, Metallurgy & Exploration, 1995)
Nickel is present in a number of gold ores in Australia, Africa and the United States. The effects and behaviour of the nickel during the cyanidation and adsorption processes, and also during the elution and electrowinning processes have been examined by a number of researchers, usually as a part of a larger investigation. This paper examines the available data on the behaviour and effect of nickel during cyanidation and its associated unit processes. The presence of nickel is often not considered to be particularly important as it does not cause the same degree of problems across the circuit as those experienced in the presence of copper. It can however lead to increased cyanide consumption during leaching, and reduced adsorption of gold onto carbon. A proportion of nickel cyanide may be removed from carbon prior to elution by carrying out a hot (90° C) acid wash. The nickel which remains on the carbon will be partially eluted during the main elution step, and, dependent on its concentration in the pregnant solution, part of it may be deposited during electrowinning. There is always a risk that any nickel remaining on the carbon after the elution step will be reduced to metallic nickel during the regeneration step. This may ultimately result in an increasing base level of nickel on the carbon, as metallic nickel is insoluble in both cyanide and hydrochloric acid.